Atenção e cuidado em práticas de encantamento: políticas de produção de vida interespécie - Giori, Leonardo Cetto (2023)
This research is dedicated to the cultivation of an autocartography based on encounters with non-human lives in the multi-species territory of the Atlantic Rainforest, looking at the study of attention from the point of view of inventive cognition and the concept of care as an ontological requirement for relational worlds as a way of approaching otherness. Thinking about compositions, experimentations and processualities through these studies, we tried to sew together in the field and in writing, in intentions, emotions, thoughts and analysis, an antidote against forgetfulness, against disenchantment. In an attempt to find ways to counteract the disenchantment of the world and those who live in it from a multi-species perspective, we have advocated the possibility of recognizing and creating other worlds where we can articulate the manufacture of new ways of engaging humans with the world. So that we can think about collective intelligence and imagine new policies of relationality and affectivity between human and non-human lives that help us resist the atrocities of anthropocentrism that are dragging us into contemporary socio-environmental collapse.